Prevalence of Interceptive Contacts in Centric Relation in Complete Denture Wearers - P. Atashrazm; MH. Dashti; MR. Mobeinie (Tehran University of Medical Sciences, 2008)
Objective: Interceptive contacts in complete denture cause some side effects. To our knowledge, however, no comprehensive reports exist on the prevalence of interceptive contacts after complete denture placement. The aim of the present study was to investigate the prevalence of interceptive contacts in inserted complete dentures and its associated factors. Materials and Methods: This cross sectional study was conducted on 52 patients receiv-ing complete denture treatment. Factors such as gender, ridge relationship and its extent, and occlusal scheme were recorded for each patient. Whether the clinical remounting had been done was also recorded. The status of interceptive contacts was determined extra-orally and qualitatively. Chi-square test served for statistical analysis. The results were considered highly significant at P<0.0001 and significant at P<0.05. Results: Out of 52 patients, 15 (28.8%) showed interceptive contacts. No statistically sig-nificant association was found between interceptive contacts and gender, ridge relation-ship, the extent of residual ridge resorption, or occlusal scheme. Clinical remount had been performed only for one of the dentures with interceptive contacts. Highly significant rela-tionship existed between clinical remounting and absence of interceptive contacts (P<0.0001). Conclusion: Within the limits of this study, interceptive contacts were noticeable. Clinical remounting seemed to play an important role in preventing interceptive contacts.